Spatial Dimensions Of The Injuries Of Children In Basra Governorate With Some Cancerous Diseases - Al-Sarayefi, Ali Nasser Abdullah; Razzaq, Farah Falah Abdul (Adolescência e Saúde, 2026)
The study aims to highlight the importance of cancer diseases that affect children under the age of fifteen in Basra Governorate for the period from 2010 to 2023. Children were classified into three age groups (0-4) years, (4-9) years, (10-14) years. The study found that cancer diseases affect children of all age groups. The age group (0-4) years recorded the highest incidence of cancer diseases, amounting to (781) cases occupied by females (355) and males (426). The category (10-14) years ranked second with (719) injuries. The share of females was (305), while males (414) injuries. As for the category (5-9) years, the number of injuries was (606) injuries. Females occupied (272) injuries and males (334) injuries. The center of Basra Governorate (Basra District) recorded the first number of injuries, amounting to about (958) injuries, to occupy Al-Zubair District second with a number of (380) injuries, while Al-Fao District recorded the lowest number of cases in the study area with (29) injuries. It turned out that bone marrow cancer ranked first among cancer diseases with a number of (372) injuries, brain and brain cancer with a number of (173) injuries, and adrenal and lymphoma cancer with a number of (79) injuries, while bone, connective and soft tissue cancer were (67, 26) injuries in succession, and it was found that Basra district ranked first with types of cancer diseases to occupy Al-Zubair district second, while Al-Faw district came last.